Lights and shadows of the implementation of the Victims' Agreement in Colombia (Mayéutica Revista Científica de Humanidades y Artes, 2024)
The implementation of the Peace Agreement in Colombia has been surrounded by difficulties and challenges, in particular, in relation to the Agreement on victims of the conflict. In this sense, it is opportune to take some elements of the road traveled and collect some considerations that contribute to the construction of a stable and lasting peace in the country from the integral reparation to the victims. This text aims to analyze the implementation of the Agreement on Victims signed between the Government of Colombia and the Revolutionary Armed Forces of Colombia People's Army (FARCEP) within the framework of the Final Agreement, based on reports from national and international organizations. The selection of these sources is made for their recognized institutional character and for their trajectory in accompaniment and reflection for the construction of peace in the world. The analysis shows that the implementation of the Agreement on victims presents advances and challengesregarding legislation to comprehensively compensate victims, institutional strengthening and adequate financing for the operation of the Integral System of Truth, Justice, Reparation and NonRepetition (SIVJRNR).
Keywords: Peace agreement; victims; reconciliation; comprehensive reparation; conflict